Neotropical Deer Ked or Neotropical Deer Louse Fly, Lipoptena mazamae Rondani (Insecta: Diptera: Hippoboscidae) - William H. Kern, Jr. (EDIS, 2023)
The Neotropical deer ked, Lipoptena mazamae Rondani, is a common ectoparasite of the white-tailed deer (Odocoileus virginianus) in the southeastern United States. The louse flies (Hippoboscidae) are obligate blood-feeding ectoparasites of birds and mammals. Both adult males and females feed on the blood of their host. They are adapted for clinging to and moving through the plumage and pelage of their hosts. Strongly specialized claws help them cling to the hair or feathers of their particular host species. Deer keds have wings when they emerge from their puparium, but lose their wings once they find a host (deer). This document is EENY-308, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: September 2003.